Post-Classical Philosophical Commentaries/Glosses: Innovation in the Margins - Ahmed, Asad Q. (Oriens, 2013)
This article investigates the nature of the post-classical (ca. 600–1300/1200–900) commentary/gloss genre in the maʿqūlāt (rationalist disciplines). It does so by looking closely at the process of philosophical growth in the tradition of a celebrated text on logic, the Sullam al-ʿulūm of Muḥibballāh al-Bihārī (d. 1118/1707), that inspired more than ninety commentaries, glosses, and notes in Arabic, Persian, and Urdu in the course of two centuries. Among other things, the article concludes that, from the very beginning, the authors of the main text and of its commentaries/glosses posited the lemmata as sites of philosophical conflict and dispute (masāʾil)—though these lemmata were also seamlessly interwoven into the larger aims of philosophical works. These open spaces of philosophical dialectic stood in place of a vibrant culture of debate that was responsible for the diachronic and synchronic dynamism of post-classical philosophy. In this article, the detailed analysis of a minor lemma and its fate in the hands of some prominent commentators and glossators sheds light on the complex layers of the intertextuality of commentaries and glosses, on structures of textual authority, on the nature of the self-gloss, on the fine line between commentarial critique and defense, and on the meaning of verification (taḥqīq). Finally, the technical assessment of the philosophical arguments also reveals how the mode of argumentation required by the very framework of the commentary/gloss genre resulted in the production of novel philosophical theories.